Absolute monocytosis at diagnosis correlates with survival in diffuse large B‐cell lymphoma—possible link with monocytic myeloid‐derived suppressor cells. Issue 2 (20th June 2012) - Tadmor, Tamar; Fell, Rona; Polliack, Aaron; Attias, Dina
Abstract Some patients with lymphoma have monocytosis at diagnosis, but its significance is unclear. The recently recognized subpopulation, monocytic myeloid‐derived suppressor cells (M‐MDSCs), has immunoregulatory function, suppresses host anti‐tumour immunity and plays a role in cancer tolerance. Data from 91 untreated patients with diffuse large B‐cell lymphoma (DLBCL) were evaluated for monocytosis >1000/mm3 at diagnosis and its significance compared with a number of well‐established prognostic factors for DLBCL including age, stage, gender, B symptoms, extranodal sites, LDH and CRP levels, bone marrow involvement and International Prognostic Index (IPI) score. In 23 of these patients with DLBCL and 15 healthy controls, the proportion of M‐MDSCs in the peripheral blood was determined by flow cytometry. Monocytosis was found in 17.6% of the patient cohort examined. In the multivariate analysis, bone marrow involvement, IPI score and monocytosis were the only independent prognostic factors seen to be associated with decreased progression free and overall survival. Patients with DLBCL had on average increased M‐MDSCs counts at diagnosis compared with controls, which returned to normal after achieving remission. In conclusion, monocytosis was identified as an independent prognostic factor in DLBCL and correlated with worse overall survival. The significant increases in the M‐MDSCs pool observed in some of the cases examined may possibly help to explain why monocytosis is associated with poor outcome in these patients. Copyright © 2012 John Wiley & Sons, Ltd.